PEMANFAATAN CACING TANAH (Lumbricus rubellus) PADA PENDEDERAN LOBSTER AIR TAWAR (Cherax quadricarinatus) DENGAN SISTEM RESIRKULASI - Sari, Indah Permata; Nurhatijah, Nurhatijah; Fauzi, Ahmad; Azhar, Rossy; Nuraida, Nuraida; Abdan, Mu'amar (MAHSEER: Jurnal Ilmu-Ilmu Perairan dan Perikanan, 2024)
Recirculation systems are intensive cultivation methods that offer an attractive alternative to extensive systems for lobster farming. This study aims to evaluate the utilization of earthworms (Lumbricus rubellus) in the juvenile rearing of freshwater lobsters (Cherax quadricarinatus) using a recirculation system. The research was conducted at the Wet Laboratory of the Seed and Fish Feed Production Technology Study Program, Politeknik Indonesia Venezuela, from October to November 2022. The experimental design used was a Completely Randomized Design (CRD) non-factorial, consisting of 4 treatments and 4 replications: A (control), B (10% of biomass), C (15% of biomass), and D (20% of biomass). The results showed that treatment D (20% of biomass) produced the highest absolute weight growth, with an average of 12.0 g, while treatment A (control) had the lowest weight with an average of 1.2 g. The highest absolute length growth was also observed in treatment D, with an average of 4.5 cm, while treatment A had the lowest length growth at 0.7 cm. The highest feed conversion ratio (FCR) was achieved by treatment B (10% of biomass) with an average of 2.57, whereas the lowest FCR was observed in treatment D with an average of 1.63. The highest molting frequency over 30 days was recorded in treatment D, while the lowest molting frequencies were found in treatments A and B. ANOVA test results indicated that the earthworm treatments significantly affected absolute weight growth, absolute length growth, feed conversion ratio (FCR), and molting frequency of the lobsters over 30 days. However, there was no significant effect on the survival rate (SR) of the lobsters.